تشكيل شخصية الأمير عبد القادر في رواية الجزائرية رواية الامير لواسيني الاعرج أنموذجا - كرباع، علي; زغدي، سعاد; زغدي، سهام; بيات، الحادة (University of Eloued جامعة الوادي, 2024)
نهدف من خلال هذه الدراسة إلى توضيح صورة شخصية "الأمير عبد القادر" الجزائري في رواية الأمير لــ"واسيني الأعرج"، فقد صوره الكاتب كقائد عسكري شجاع منحك الذي أسس دولته وجهز جيشا خاض عدة معارك ضد العدو، كما وصف الكاتب الأمير برجل الدين والأخلاق الإسلامية، فلقد حفظ القرآن وعمره إحدى عشرة عاما، اتصف بخلق التسامح والتواضع والسلم وحسن معاملته للأسرى الحربيين، كما عرف بالتصوف والزهد ومحاورة الأديان. لقد أشار "واسيني الأعرج" في روايته للكثير من الأمكنة أهمها المسجد، ساحة المعارك والسجن أو المنفى والتي أثرت على شخصية "الأمير عبد القادر" ومشاعره. This study aimed to clarify the personal image of the Algerian Emir Abdelkader. ln the novel "Al-Amir" by Wassini Al-Araj, the author portrayed him as a brave and an astute military leader who founded his state and made an army. He fought several battles against the enemy. The author also described the prince as a man of religion and Islamic ethics. He memorized the Quran at the age of eleven. He was characterized by tolerance, humility, peace, and kindness towards prisoners of wars.He was also known for his Sufism, asceticism, and interreligious dialogue. ln his novel, Wassini Al-Araj metioned many places. Thr most important ones are the mosque, the battlefield, and the prison or exile which affected the character and emotions of Emir Abdelkader
813/ 004
Keywords: تشكيل - الشخصية -الرواية - رواية الأمير -المكان: formation; character; novel; The Prince's Novel; location